Ecotourism as a multidisciplinary conservation approach in Africa - Cheung, Hubert (THERYA, 2015)
Conservation biology addresses complex issues that require multidisciplinary solutions capable of addressing various ecological, social, cultural, economic, political and legal aspects. Compromises between biodiversity conservation and human development are inevitable given societal demands and funding constraints. Ecotourism has the potential to provide local stakeholders with socioeconomic benefits while achieving conservation objectives. Reported here is a cost-benefit analysis of of tourism in Kenya's national parks that explores issues and potentialimprovements to maximize benefits and minimize costs. Some of the issuesraised in this analysis are then explored in the wider context of conservation in Africa. In particular, conservation in Africa would benefit from a greater involvement of local stakeholders in ecotourism decision-making, the development of tourist interest in a wider range of wildlife, and a wider application of adaptive management principles.